In vitro regeneration of Garden Balsam, impatiens balsamina using cotyledons derived from seedlings - Huyop, Fahrul Zaman; Wagiran, Alina; Mohd. Taha, Aishah; Ghazali, Hamidah (Faculty of Biosciences and Bioengineering, 2009)
Garden balsam, Impatiens balsamina, is one of an important ornamental plant in Malaysia. An effort to develop a reliable tissue culture system for this Impatiens species was carried out for future genetic manipulation of this plant for useful traits. Parts of cotyledons and hypocotyl derived from different age of seedlings, from surface sterilized seeds, were subjected to shoot induction on MS media containing BAP, TDZ or combination of BAP and NAA in different ratios. Roots were developed from the above shoots on full- or halfstrength MS media containing IAA, IBA or NAA of different concentrations. Finally fully-developed plantlets were produced on hormone free MS media or full- or half-strength MS media containing specific hormones. It was observed that the most efficient shoot induction (93%) was obtained from proximal part of cotyledon derived from 7 days old seedlings on MS media supplemented with 1mg/L BAP. Roots were most efficiently produced (92%), in term of percentage and morphology, on half-strength MS media supplemented with 0.1 mg/L IAA. Further regeneration of plantlets, approximately 8-10 cm in height, was achieved after 3 weeks on hormone-free MS media. Finally, full regeneration system of Impatiens balsamina was developed, using MS media supplemented with 1 mg/L BAP for shoot and 0.1 mg/L IAA for roots, within 8 weeks in culture.